The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.4315/0362-028x-71.7.1481
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sigma B Factor in the Alkaline Tolerance Response of Listeria monocytogenes 10403S and Cross-Protection against Subsequent Ethanol and Osmotic Stress

Abstract: Many of the considerable abilities of Listeria monocytogenes to persist and grow in a wide range of adverse environmental conditions are thought to be at least partly under the control of the alternative sigma factor (sigmaB), encoded by the sigB gene. However, little is known about the role of this master regulon in the impressive ability of Listeria to persist and grow under conditions of alkaline pH. In this study, Northern blot analysis of parent Listeria mRNA revealed that alkali adaptation (pH 9.5 for 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Whole-genome microarray studies have shown 714, 411, and 355 genes of L. monocytogenes to be differentially transcribed under heat (58), cold (10), and alkali stresses (20), respectively, compared with control growth conditions. Mutational analyses have confirmed the role of alternative sigma factors in the bacterium's tolerance to all these, as well as osmotic, acid, oxidative, and ethanol stresses (9,12,18,19,41,(47)(48)(49)60). In addition, the involvement of approximately 30 other factors in the tolerance of L. monocytogenes to these stresses has been reported (54).…”
mentioning
confidence: 81%
“…Whole-genome microarray studies have shown 714, 411, and 355 genes of L. monocytogenes to be differentially transcribed under heat (58), cold (10), and alkali stresses (20), respectively, compared with control growth conditions. Mutational analyses have confirmed the role of alternative sigma factors in the bacterium's tolerance to all these, as well as osmotic, acid, oxidative, and ethanol stresses (9,12,18,19,41,(47)(48)(49)60). In addition, the involvement of approximately 30 other factors in the tolerance of L. monocytogenes to these stresses has been reported (54).…”
mentioning
confidence: 81%
“…AS also upregulated 4 regulatory proteins (RsbV, RsbW, RsbX, and RsbS) involved in the posttranslational regulation of the activity of sigB, suggesting multilevel modulation of the activities of this key regulon (Supplemental Table S1). Thus, the alkaliinduced upregulation of RsbV and RsbW observed in this study is probably responsible, at least in part, for the observed upregulation of sigB, itself the central switch in the rapid activation of a range of mechanisms that allow Listeria to survive the alkali stress challenges posed in the human gastrointestinal tract and alkali-based disinfectants used in foodprocessing systems (Giotis et al, 2008a).…”
Section: Adaptive Mechanismsmentioning
confidence: 71%
“…The significance of this operon as a central mechanism in the sophisticated adaptive mechanisms to stress has been highlighted in a wide range of bacteria (Karlin et al, 2004;Satorhelyi, 2004). In L. monocytogenes, it is involved in resistance against alkali, oxidative, osmotic, heat, bile, and acid stress (Ferreira et al, 2004;Moorhead and Dykes, 2004;Sue et al, 2004;Giotis et al, 2008a) and is also important in virulence and the ability to invade host cells (Kim et al, 2005;Rauch et al, 2005;Garner et al, 2006). As might be expected of such an important regulon, sigB is itself subject to a complex regulatory system, and this study observed that AS induced significant upregulation of three genes (lmo0889, lmo0891, and lmo0892) that encode for proteins involved in the regulation of sigB.…”
Section: Adaptive Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 A similar sigma factor σB, encoded by the sigB gene is the responsible mediator for the resistance of Gram-positive bacteria e.g., S. aureus, L. monocytogenes and Bacillus spp in many adverse environmental conditions. 27 For Escherichia coli, global stress response is triggered by the alternative sigma factor RpoS and this may result in tolerance to homologous or heterologous (i.e., cross tolerance) stresses. For instance, cells starved for carbon become resistant to hydrogen peroxide, high temperature and low pH.…”
Section: Survival In a Variety Of Environments And Virulence Expressionmentioning
confidence: 99%